2013
DOI: 10.1111/nhs.12039
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining secondary school nursing practice in Australia: A qualitative study

Abstract: This interpretive descriptive, qualitative study explored secondary school nurses' perceptions of factors that impact on their role and their views on how their role can be best supported. Nine secondary school nurses from four Department of Human Services regions in Victoria, Australia, participated in semistructured, in-depth interviews. Purposive sampling was used, with participants required to have a minimum of 2 years' experience as secondary school nurses. Data were thematically analyzed, revealing a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(5 citation statements)
references
References 36 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…As with earlier studies, specific concerns were raised regarding the time available for school nurses to provide appropriate care (Pryjmachuk et al., 2012; Seigart et al., 2013). Previous studies conducted in Australia have found that nurses describe their workloads as hectic, busy, demanding and stressful (Guzys et al., 2013; Pryjmachuk et al., 2012; Seigart et al., 2013). Similarly, studies conducted in Canada, the US and the UK have concluded that workloads of school nurses are becoming unmanageable at a time when demand for mental health care among adolescents is increasing (Baisch et al., 2011; Seigart et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As with earlier studies, specific concerns were raised regarding the time available for school nurses to provide appropriate care (Pryjmachuk et al., 2012; Seigart et al., 2013). Previous studies conducted in Australia have found that nurses describe their workloads as hectic, busy, demanding and stressful (Guzys et al., 2013; Pryjmachuk et al., 2012; Seigart et al., 2013). Similarly, studies conducted in Canada, the US and the UK have concluded that workloads of school nurses are becoming unmanageable at a time when demand for mental health care among adolescents is increasing (Baisch et al., 2011; Seigart et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The risk of fatigue and burnout among school nurses is high due to the challenging and demanding role along with the often autonomous and professionally isolating work environment (Downie et al., 2002; Guzys et al., 2013; Sendall et al., 2011). Generally, there is a lack of support available for school and community nurses (Borrow et al., 2011; Pryjmachuk et al., 2012; Sendall et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly identified roles and responsibilities are a key principle of successful school health and wellbeing approaches (NSW Department of Education 2021). A lack of role clarity has been identified as a barrier in the implementation and sustainability of other school nursing programs (Barnes et al 2004;Brooks et al 2007;Guzys et al 2013). This is likely to be particularly challenging in less traditional models of school nursing.…”
Section: Provide Initial Role Clarity But Plan To Adapt and Evolve Th...mentioning
confidence: 99%
“…Nurses must also possess sufficient knowledge and skills in order to provide person-centered care and strategies related to adolescent stress (Guzys, Kenny, & Bish, 2013).…”
Section: Introductionmentioning
confidence: 99%